2014
DOI: 10.1186/1471-2253-14-30
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral resection syndrome in elderly patients: a retrospective observational study

Abstract: BackgroundTransurethral resection of the prostate (TURP) involves the risk of transurethral resection (TUR) syndrome owing to hyponatremia. Irrigation fluid type, duration of operation, and weight of resected mass have been evaluated as risk factors for TUR syndrome. The purpose of the present study was to identify risk factors related to TUR syndrome in the elderly.MethodsAfter obtaining approval from the Institutional Review Board, data on all elderly males (aged 70 years and older) who underwent TURP under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 23 publications
1
34
0
2
Order By: Relevance
“…Our previous study also found this to be an important risk factor for TUR syndrome in older patients [12]. Such continuous drainage of irrigation fluid facilitates the removal of debris, blood, and clots from the operating field.…”
Section: Discussionmentioning
confidence: 78%
“…Our previous study also found this to be an important risk factor for TUR syndrome in older patients [12]. Such continuous drainage of irrigation fluid facilitates the removal of debris, blood, and clots from the operating field.…”
Section: Discussionmentioning
confidence: 78%
“…The incidence of TURS in patients undergoing TURP is about 0.5-10.5%. The risk is exacerbated among the elderly (up to 24%) due to decreased reserve capacity and added co-morbidities [19,] and RF adds to the difficulty of the kidneys to handle excess fluid. However, modifications in TURP such as the use of bipolar energy have resulted in significant advantages over TURP including better and greater tissue removal, less bleeding, greater visibility, better hemostasis, shorter operative time, negligible chances of TUR syndrome shorter duration of postoperative irrigation and catheterization, and shorter hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, both types of assessments must be applied to ensure a full evaluation of a patient's HRQoL. 12 113 As for achieving patient satisfaction relating to HRQoL, a detailed description of the current patients' condition and prior treatment must be clearly conveyed as it deserves. 107 Moreover, the laboratory findings could be predictors of the development of neurological and cardiovascular manifestations of TURP syndrome.…”
Section: Emotional and Psychological Factorsmentioning
confidence: 99%
“…10 The prevalence of TURP syndrome rates were 2.0% to 4.8%, respectively. 12 Another study documented the cases of TURP syndrome were 11.1% in a clinical setting. 12 Another study documented the cases of TURP syndrome were 11.1% in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation